Cost-Utility Analysis of the Integrated Care Models for the Management of Hypertension Patients: A Quasi-Experiment in Southwest Rural China - Ke, Xiatong; Zhang, Liang; Tang, Wenxi (Frontiers in Public Health, 2021)
Background: Hypertension has become the second-leading risk factor for death worldwide. However, the fragmented three-level “county–township–village” medical and health-care system in rural China cannot provide continuous, coordinated, and comprehensive health care for patients with hypertension, as a result of which rural China has a low rate of hypertension control. The purpose of this study is to explore the costs and benefits of an integrated care model using three intervention modes-multidisciplinary teams (MDT), multi-institutional pathway (MIP), and system global budget and performance-based payments (SGB-P4P)-for hypertension management in rural China. Methods: A Markov model with one year per cycle was adopted to simulate the lifetime medical cost and quality-adjusted life-years (QALYs) for patients. The interventions included Group 1 (MDT+MIP), Group 2 (MDT+MIP+SGB−P4P), and the control group (usual care). We used theICER, NMB, and NHB to make economic decisions, and a 5% discount rate. One-way and probability sensitivity analyses were performed to test model robustness. Results: (1) Compared with the control group, Group 1 yielded an additional 0.068 QALYs and an additional cost of $229.99, resulting in an ICER of $3,373.75/QALY, the NMB was −$120.97, and the NHB was −0.076 QALYs. (2) Compared with the control group, Group 2 yielded an additional 0.545 QALYs, and the cost decreased by $2,007.31, yielding an ICER of −$3,680.72/QALY. The NMB was $2,879.42, and the NHB was 1.801 QALYs. (3) Compared with Group 1, Group 2 yielded an additional 0.477 QALYs, and the cost decreased by $2,237.30, so the ICER was −$4,688.50/QALY, the NMB was $3,000.40, and the NHB was 1.876 QALYs. The one-way sensitivity analysis showed that the most sensitive factors in the model were utility and cost. The probability sensitivity analysis showed that when willingness to pay was $1,599.16/QALY, the cost-effectiveness probability of Groups 1 and 2, and the Control Group were 0.008, 0.813, and 0.179, respectively. Conclusions: The integrated care model with performance-based prepaid payments was the most beneficial intervention, whereas the general integrated care model (MDT+MIP) was not economic. The integrated care model (MDT+MIP + SGB-P4P) was suggested for use in the community management of hypertension in rural China.